Systemic health care failure as a symptom of Market Failure in Sierra Leone - Emerson Abraham Jackson (Southern African Journal of Public Health (incorporating Strengthening Health Systems), 2019)
The article has provided an unbiased discourse on the subject of market failure, with focus on the health service system (HSS) in Sierra Leone. It is acknowledged that market failure in the country's HSS is a real concern that has gone unchecked for decades by successive governments. In view of the prevailing conditions, it is hereby noted in this article that government failure is to be blamed for poor conditions experienced in the health sector. The issue of squeezed funding to manage the HSS must be revisited in order to address critical concerns of health in the country. Most important to this is the continued existence of rent-seeking which health professionals have thrived on, thereby making it much more of a free riding venture on which health professionals have hedged on to increase profit share, while (unknowingly) depriving the poor and needy from being able to utilise affordable services in state funded hospitals / health care centres. While it is also a fact that rent-seeking has been on the rise, it is also noted in the article that conditions of service has fallen behind of what is needed for health professionals to maintain decent living, and hence the need for government to intervene in mitigating perpetual government failure in the country's HSS. – – L'article a fourni un discours impartial sur le sujet de la défaillance du marché, en mettant l'accent sur le système de services de santé en Sierra Leone. Il est reconnu que la défaillance du marché des systèmes de santé du pays est une préoccupation réelle qui n'est pas contrôlée depuis des décennies par les gouvernements successifs. Compte tenu des conditions qui prévalent, il est noté dans cet article que l'échec du gouvernement doit être imputé aux mauvaises conditions du secteur de la santé. La question du financement insuffisant pour gérer le RSS doit être réexaminée afin de répondre aux préoccupations cruciales de la santé dans le pays. Le plus important pour cela est la persistance de la recherche de rente sur laquelle les professionnels de la santé ont prospéré, ce qui en fait bien davantage une aventure gratuite sur laquelle les professionnels de la santé se sont tournés pour accroître leur part des profits, tout en privant (à leur insu) les pauvres et les nécessiteux. de pouvoir utiliser des services abordables dans des hôpitaux / centres de santé financés par l'État. Il est également vrai que la recherche de rente est à la hausse, mais il est également noté dans l'article que les conditions de service ont pris du retard par rapport aux besoins des professionnels de la santé pour maintenir une vie décente, d'où la nécessité pour le gouvernement d'intervenir dans l'atténuation de l'échec gouvernemental perpétuel dans le RSS du pays.
Keywords: H40; Q30; 330; Market Failure; Health Care System; Rent-seeking; Sierra Leone